2019
DOI: 10.1539/eohp.2019-0010-gp
|View full text |Cite
|
Sign up to set email alerts
|

Referencing the body for mood state regulation: an examination of stress management using Dohsa-hou as a primary prevention program for nurses

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made. AbstractObjectives: Stress management for human service professionals remains an international issue. Methods: We conducted a primary prevention program using Dohsa-hou designed to provide early-career nurses with an understanding o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“… Haramaki et al (2019) also observed an in vivo exposure-based ability for long-term hemodialysis patients to address issues with self-regulatory fatigue from chronic pain by using Dohsa-hou tasks. Furthermore, in stress management applications of Dohsa-hou, Abe et al (2019) observed changes in mood states, especially vigor, in a sample of nurses at-risk for burnout. The role of movement is central to this attentional form of self-regulation and might extend to meditative movement practices with similar elements (e.g., qigong, yoga, or tai chi in applied contexts of rehabilitation or behavioral change).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“… Haramaki et al (2019) also observed an in vivo exposure-based ability for long-term hemodialysis patients to address issues with self-regulatory fatigue from chronic pain by using Dohsa-hou tasks. Furthermore, in stress management applications of Dohsa-hou, Abe et al (2019) observed changes in mood states, especially vigor, in a sample of nurses at-risk for burnout. The role of movement is central to this attentional form of self-regulation and might extend to meditative movement practices with similar elements (e.g., qigong, yoga, or tai chi in applied contexts of rehabilitation or behavioral change).…”
Section: Discussionmentioning
confidence: 99%
“…The Japanese psychotherapy known as Dohsa-hou (“body movement method”) has shown indicators of effectiveness in clinical settings and community applications. The growing evidence base suggests that the approach confers regulation over pain toward daily life functioning ( Haramaki et al, 2019 ), relaxation-based coping with mood states as a form of stress management ( Abe et al, 2019 ; Kuwashima and Yoshikawa, 2020 ), and body-mediated communication between clients and therapists ( Fujino, 2017 ; Kawano and Fujino, 2021 ). Hypothesis formation has advanced about the role of cognition from experiments on the postural control of elderly adults ( Adachi, 2015 ) and gains in interoceptive and proprioceptive awareness in Dohsa-hou applications toward understanding its fit with toolboxes of meditative movement ( Kabir et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It induces changes in a patient's experience through movements and physical interactions, even in individuals with severe intellectual and multiple disabilities 17,18 . Dohsa‐hou has also been used both as a treatment for psychological symptoms and a preventive measure for mental distress 18–20 . Although its effectiveness has not been well investigated in interventional studies, such as clinical trials, this approach has been clinically used in Asian countries for people with mental illness and emotional disorders 16,18,21,22 …”
Section: Introductionmentioning
confidence: 99%